Studying the heterogeneous pathogenesis of canine diabetes: Observational characterization of an island population. Issue 4 (23rd February 2021) - Brito‐Casillas, Yeray; Melián, Carlos; Holder, Angela; Wiebe, Julia C; Navarro, Ana; Quesada‐Canales, Óscar; Expósito‐Montesdeoca, Ana B; Catchpole, Brian; Wägner, Ana M
Abstract: Background: Canine diabetes mellitus has mostly been studied in northern European, Australian and American populations, whereas other regions have received less attention. Objectives: We evaluated the epidemiological, clinical and histopathological features of diabetic dogs in Gran Canaria, Spain. Methods: Prevalence and incidence were estimated. Clinical features were analysed, and serum and genomic DNA were obtained. Dogs with presumed idiopathic or immune‐mediated diabetes, were DLA‐typed and antibodies against GAD65 and IA‐2 were assessed. Pancreases from ten diabetic dogs were examined and compared with pancreases from non‐diabetic dogs. Results and conclusions: Twenty‐nine diabetic dogs were identified in a population of 5, 213 (prevalence: 0.56%; incidence: 0.37%). Most were female (79%) and sexually intact (87% of females, 83% of males). Diabetes secondary to dioestrus (55.2%) and insulin‐deficient diabetes (20.7%) were the most frequent types. Antibodies against GAD65 and IA‐2 were identified in two out of five cases and DLA‐genotyping revealed novel haplotypes. Breed distribution differed between diabetic and non‐diabetic dogs. Reduced number of pancreatic islets and β‐cell mass were observed, with vacuolation of islet cells and ductal epithelium. In this population, where neutering is not standard practice, diabetes secondary to dioestrus is the most frequent diabetes subtype. Genetic susceptibility also differed from previous studies. These results support the heterogeneous pathogenesis of canine diabetes. Abstract : After evaluating the epidemiological, clinical and histopathological features of diabetic dogs from the Canary Islands, in this population the most common type of diabetes is dioestrus diabetes, and the breed‐specific risk of diabetes differed from previous studies. These results, obtained in a relatively small population, support the heterogeneous pathogenesis of cDM.